Great American Smokeout [Moakley-Boucher fire-safe cigarette bill] (Tufts Archival Research Center, 2007)
Marginalia; Memo from Samuel Chilcote to members of TI Executive Committee informing them of House and Senate passage of Moakley-Boucher fire-safe cigarette bill, HR 293. Includes response to the press, supporting the bill. Also includes article from Regulation, Economics and Law, July 20 1990 issue, on the bill.